Management of Improving the Quality of Education Through the 2013 Curriculum at Fadhilatul Qur'an Sampang High School - Intan Dwi Permatasari; Ach Syafiq Fahmi; Tika Hestiarini Utami; Ali Nurhadi (al-Afkar, Journal For Islamic Studies, 2025)
The purpose of this study is to ascertain how the Fadhilatul Qur'an Sampang high school is managing to raise the standard of instruction using the 2013 curriculum. Qualitative research using a field study technique is the research methodology employed. The methods of gathering data include, interviews, and observation. The 2013 curriculum's management of raising educational standards is divided into three phases: planning, implementing, and evaluating. The study's findings demonstrate that, first, management planning for raising educational standards through the 2013 curriculum explains how to create learning implementation plans (RPP) that will help students learn successfully. Secondly, management is implemented for raising educational standards through the 2013 curriculum. The three management evaluations for increasing educational quality through the 2013 curriculum were conducted using three assessment criteria: cognitive, affective, and psychomotor.